Comparative study from a chemical perspective of two- and three-step disinfection techniques to control Clostridium difficile spores - Massicotte, Richard; Ginestet, Pauline; Yahia, L’Hocine; Pichette, Gilbert; Mafu, Akier Assanta (International Journal of Infection Control, 2011)
Around the world, the presence of Clostridium difficile in hospital environments remains a great concern. To control the spread of this Gram-positive bacterium requires a better understanding of the various chemical interactions between the components of the bacterium and the surfaces to be cleaned. The objective of the present study was to compare, from a chemical perspective, two surface disinfection techniques and the use of two dilutions (1/20 and 1/10) of a 5% sodium hypochlorite solution. The following two cleaning-disinfection procedures were used: first, a two-step technique consisting of the use of a detergent-disinfectant (thirdgeneration quaternary ammonium) followed by 5% household sodium hypochlorite; and second, a three-steptechnique consisting of the above steps plus a water rinse step between the detergent-disinfectant step and the disinfection product step. The results of the study show that the three-step technique with a 1/10 dilution of 5% sodium hypochlorite solution creates a chemical environment that provides greater disinfection potential compared to the two-step technique.